Hard-to-Treat Areas in Psoriasis: An Underevaluated Part of the Disease - Adina-Mihaela Lupulescu; Alexandra Petruța Savu; Ştefana Bucur; Elena-Daniela Şerban; Sanda Popescu; Maria Magdalena Constantin (Life)
Hard-to-treat areas in psoriasis vulgaris, i.e., the scalp, nails, genital area, palms, and soles, are less commonly diagnosed and treated. Our understanding of the complex etiopathogenesis and treatment of psoriasis vulgaris has advanced considerably in recent years. After performing an English literature search, the present article is a comprehensive review based on several relevant articles. The articles included met the following criteria: they mentioned the “hard-to-treat areas, special sites, difficult-to-treat areas” or the specific body location of psoriasis, and they reported the psoriasis prevalence and/or patients’ quality of life. Despite the extensive information about psoriasis, there are still many limitations and challenges regarding the appropriate approach to psoriasis in these special locations. But emerging directions such as precise severity scores, new biomarkers for disease monitoring, and treatment decisions or forthcoming therapies represent solutions to improve the lives of those affected. Although they affect a small area, the impact on the quality of everyday life is significant, causing physical and mental disability. In this review, we try to highlight the need for more information about hard-to-treat areas, including their prevalence, a more rapid diagnosis, and a correct classification based on their real severity and their specific treatment before a significant impact on patients’ quality of life occurs. By presenting these challenges, we hope to contribute to efforts at improving disease control.